Penerapan Model Discovery Learning Untuk Meningkatkan Keterampilan 4C Kelas V Pada Tema 3 Subtema 1 Di SDN 10 Banda Aceh - Dela Selvia; Mislinawati Mislinawati; Linda Vitoria (Elementary Education Research, 2023)
This research is motivated by teachers who have not implemented an active learning model which results in learning not going well. At this time the world of work also demands changes in skills. communication skills, collaboration, critical thinking and problem solving, creativity and innovation, these skills are important in entering 21st century life. The purpose of this research is to find out the Application of the Discovery Learning Model in Improving Class V 4C Skills in Theme 3 Sub-theme 1 at SDN 10 Banda aceh. This type of research is classroom action research (CAR). This research was conducted at SDN 10 Banda Aceh, Banda Aceh City. The research subjects were class V (five) teachers and 28 students. Data collection techniques in this study were written tests, observations, and documentation. The results of this study are: 1) The application of the Discovery Learning model to improve learning outcomes in 4C skills class V on theme 3 sub-theme 1 at SDN 10 Banda Aceh has been well implemented, this is evidenced by the completeness of student learning outcomes which have increased from pre-cycle results with a percentage of 71.42%, increased to 78.57%, then in the second cycle it increased with a percentage of 96.42%. 2) Teacher activity in improving class V 4C skills on theme 3 sub-theme 1 for students at SDN 10 Banda Aceh is already very good, this can be proven by the results of observations of cycle I teacher activities during two meetings, the first meeting was in the good category, the both categories were good, then the results of observations of teacher activity cycle II increased more, namely during the two meetings the total score of the first meeting and both categories were very good. 3) The activities of students in improving the 4C skills of class V on theme 3 sub-theme 1 at SDN 10 Banda Aceh have been carried out very well, this can be seen from the results of observations of student activities in cycle I, the first meeting was in good category, the second meeting was in good category, then at the observation results of cycle II student activity increased more that is, the first meeting was very good category, the second meeting was very good category. The conclusion in this study is that the application of the discovery learning model to improve the 4C skills of fifth grade students on theme 3, sub-theme 1 at SDN 10 Banda Aceh is very good.